Managerial Blurring of Employee Goals - Gyula J. Nagy; Isabelle Walsh (M@n@gement)
Many researchers and practitioners believe that the lack of specificity of employee goals is detrimental to the effectiveness of performance management in firms. Using an inductive grounded theory approach, this study identifies two managerial factors that could impact negatively goal specificity in real-life corporate environments. First, ‘goal blurring’ is a counterintuitive purposeful managerial behavior that results in blurred employee goals being set during annual reviews. Second, ‘specifying capability’ incorporates factors that can result in a lower level of specificity of employee goals with no purposeful intent. The findings reveal two main reasons managers set less specific goals: (1) limited capability and (2) choice to purposefully blur employee goals to maintain flexibility in evaluating their subordinates. While non-purposeful blurring occurs because of circumstances that make setting specific goals difficult and limit the capabilities of managers to do so, purposeful blurring of goals occurs with the main aim of maintaining flexibility in evaluating employees. As a result, blurred goals are set for employees despite managers’ awareness of the benefits of setting specific goals, which is supported by extensive research and management practice. Our work reveals the purposeful managerial blurring of employee goals, a phenomenon that has a significant impact on firm performance, though it has not been previously identified as such, or explained.